2009
DOI: 10.1007/s11325-009-0315-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine production from peripheral blood mononuclear cells and polymorphonuclear leukocytes in patients studied for suspected obstructive sleep apnea

Abstract: In patients showing similar prevalence of major cardiovascular risk factors and cardio-metabolic therapies, differing for the presence or absence of OSA, cytokine productions from PBMC and PMN were similar and were not modified during cPAP therapy. Studies designed to investigate OSA-associated inflammation should carefully match the control group subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
(79 reference statements)
0
15
0
Order By: Relevance
“…Carniero et al 2009 [63] had a very small sample population (7) and showed that CPAP usage over 3 months decreases serum TNF-α, though not significantly. Guasti et al 2009 [74] also had a small sample population (only 16) and many of the patients had other comorbidities, such as elevated BMI. In addition to a small sample population (16) and patients having high BMIs, Vgontzas and colleagues [78] noted that there were discrepancies in the compliance of the patients using CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…Carniero et al 2009 [63] had a very small sample population (7) and showed that CPAP usage over 3 months decreases serum TNF-α, though not significantly. Guasti et al 2009 [74] also had a small sample population (only 16) and many of the patients had other comorbidities, such as elevated BMI. In addition to a small sample population (16) and patients having high BMIs, Vgontzas and colleagues [78] noted that there were discrepancies in the compliance of the patients using CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…There was heterogeneity in this endpoint (df (Q) 31, p < 0.0001, I 2 = 96.4) (Figure 1). [56][57][58][59][60][61][62][63][64][65][66][67][68] The second analysis was performed with studies reporting OSA patients in groups (mild, moderate, or severe): standardized mean difference ranged from -0.18 to 8.59. The pooled mean difference was calculated to be 1.07 (LL 0.60 to UL 1.54, p < 0.0001).…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…Snoring is associated with cytokine release from blood cells, and promotes inflammation [90]. Snoring involves vibration of the soft palate, pharyngeal walls, epiglottis and the tongue, and causes lesions of the UA mucosa, pharyngeal muscles, and their innervating nerves [91][92][93].…”
Section: Hypothermia and Inflammationmentioning
confidence: 99%